Translation and cross-cultural adaptation of the International Trauma Questionnaire for use in Brazilian Portuguese - Donat, Júlia Candia; Lobo, Nathália dos Santos; Jacobsen, Gabriela dos Santos; Guimarães, Eduardo Reuwsaat; Kristensen, Christian Haag; Berger, William; Mendlowicz, Mauro Vitor; Lima, Eduardo de Paula; Vasconcelos, Alina Gomide; Nascimento, Elizabeth (São Paulo Medical Journal, 2019)
BACKGROUND: The most recent editions of diagnostic manuals have proposed important modifica-tions in posttraumatic stress disorder (PTSD) criteria. The International Trauma Questionnaire (ITQ) is the gold-standard measurement for assessing PTSD and complex PTSD in accordance with the model of the 11th International Classification of Diseases (ICD-11). OBJECTIVE: The aim of this study was to adapt the ITQ for the Brazilian context. DESIGN AND SETTING: The translation and cross-cultural adaptation of the ITQ for use in Brazilian Portu-guese was performed in trauma research facilities in Porto Alegre, Rio de Janeiro and Belo Horizonte, Brazil. METHODS: The adaptation followed five steps: (1) translation; (2) committee synthesis; (3) experts’ evalu-ation through the content validity index (CVI) and assessment of interrater agreement though kappa sta-tistics; (4) comprehension test with clinical and community samples (n = 35); and (5) final back-translation and authors’ evaluation. RESULTS: Two independent translations were conducted. While working on a synthesis of these transla-tions, the committee proposed changes in six items to adapt idiomatic expressions or to achieve a more accurate technical fit. Both the expert judges’ evaluation (CVI > 0.7; k > 0.55) and the pretest in the target population (mean comprehension > 3) indicated that the adapted items were adequate and comprehen-sible. The final back-translation was approved by the authors of the original instrument. CONCLUSION: ITQ in its Brazilian Portuguese version achieved satisfactory content validity, thus providing a tool for Brazilian research based on PTSD models of the ICD-11.